Marianna Gula, Mária Kurdi, István D. Rácz, eds. The Binding Strength of Irish Studies. Festschrift in Honour of Csilla Bertha and Donald E. Morse. Debrecen: Debrecen UP, 2011. 309 pages. - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2012)
A Festschrift is a kind of book that celebrates outstanding scholars’ achievement on special occasions like birthdays by collecting articles, essays, sometimes literary pieces and miscellania from friends and colleagues. The book in hand is highly unique even within this category as it is a joint Festschrift in honour of the distinguished scholars Csilla Bertha and Donald E. Morse, who are both respected and acclaimed scholars in the field of Irish Studies understood in a broad sense. In 2011 they had been married for twenty-five years and, coincidentally, were celebrating a 65th birthday (Csilla’s) and a 75th birthday (Donald’s) early that year. The three editors of the volume, close colleagues and fellow scholars of Csilla and Donald, seem to have found it an exceptional opportunity to mark these anniversaries by one book for the two, which is a most appropriate decision in this case. As the preface to the honorary essays claims, the two were “literally brought together by Irish Studies, because it was at the IASAIL Conference of Graz in 1984 that they first met and then got married in 1986. Over the years their love for each other and their shared devotion to Irish literature and culture have proven to be mutually strengthening, a both energizing and uniquely prosperous combination at the same time” (11).